GLP-1 receptor agonist-associated tumor adverse events: A real-world study from 2004 to 2021 based on FAERS - Yang, Zheng; Lv, Yuhuan; Yu, Meng; Mei, Mei; Xiang, Linyu; Zhao, Subei; Li, Rong (Frontiers in Pharmacology, 2022)
Background: GLP-1 receptor agonists (GLP-1RA) have demonstrated cardiovascular benefits, but the relationship between GLP-1RA and tumors is controversial. Recently, clinical trials reported higher rates of malignancy with semaglutide than control group. As real-world evidence of GLP-1RA-associated tumor risk is very limited, we explored the association of GLP-1RA and all types of neoplasms by mining the FDA Adverse Event Reporting System (FAERS) database. Methods: The FAERS data from the first quarter (Q1) of 2004 to the second quarter (Q2) of 2020 in the AERSMine were extracted to conduct disproportionality analysis, which was used by the proportional reporting ratio (PRR) to assess the relationship between GLP-1RA and all types of neoplasms. Then, the details of disproportionate GLP-1RA-associated tumor cases from Q1 2004 to Q2 2021 in the FAERS Public Dashboard were collected to analyze demographic characteristics. Results: A total of 8718 GLP-1RA-associated tumors were reported. Excluding cases with pre-existing tumors, other glucose-lowering drugs, and other GLP-1RA-related adverse events, diabetes cases with GLP-1RA as the main suspected drug were selected. GLP-1RA did not cause a disproportionate increase in all tumor cases (PRR 0.83) at the SOC level, and there was also no increase in most types of tumors associated with GLP-1RA at the HLGT/HLT levels. Significant signals were detected between GLP-1RA and certain tumors, including thyroid cancers [medullary thyroid cancer (PRR 27.43) and papillary thyroid cancer (PRR 8.68)], pancreatic neoplasms malignant (PRR 9.86), and islet cell neoplasms and APUDoma NEC (PRR 2.86). The combination of GLP-1RA with dipeptidyl-peptidase IV inhibitors (DPP4i) perhaps caused the increased reporting rate in some tumors. Conclusion: Our study provided new real-world evidence for oncology safety information of GLP-1RA. Given the wide use of GLP-1RA, clinicians should be well informed about important potential adverse events. Our pharmacovigilance analysis also prompted clinicians to raise concerns about potential tumor-related adverse effects when combining GLP-1RA with DPP4i.